การวัดปริมาณงานและกำหนดอัตรากำลังบุคลากร ด้านเภสัชกรรมโรงพยาบาล : กรณีศึกษาโรงพยาบาลมัญจาคีรี จังหวัดขอนแก่น - วัฒนาโภคสิน จุฑามาส; ดาวสดใส ไพบูลย์ (MBA-KKU Journal, 2016)
การวิจัยนี้เป็นการวิจัยเชิงประยุกต์ โดยมีวัตถุประสงค์เพื่อวัดปริมาณงานและกำหนดอัตรากำลังของบุคลากรด้านเภสัชกรรมโรงพยาบาล ของกลุ่มงานเภสัชกรรมโรงพยาบาลมัญจาคีรี อำเภอมัญจาคีรี จังหวัดขอนแก่น ซึ่งงานด้านเภสัชกรรมโรงพยาบาลประกอบด้วยงาน 8 งาน ได้แก่ งานบริหารทั่วไป และพัฒนาคุณภาพ งานบริหารเวชภัณฑ์ งานคุ้มครองผู้บริโภค งานเภสัชกรรม ปฐมภูมิ งานเภสัชกรรมคลินิก งานบริการจ่ายยาผู้ป่วยนอก งานบริการจ่ายยา ผู้ป่วยใน และงานผลิตเภสัชกรรมดำเนินการศึกษารายละเอียดลักษณะงาน และผู้ปฏิบัติงาน ในแต่ละงานย่อยของงานเภสัชกรรมโรงพยาบาล ทำการวัด เวลามาตรฐานการทำงานในงานย่อยดังกล่าวโดยใช้ผู้เชี่ยวชาญ เพื่อกำหนดเวลามาตรฐานในการทำงานในแต่ละงานย่อย คำนวณปริมาณงานโดยการ ใช้เวลามาตรฐานการทำงานคูณด้วยจำนวนผลงานในแต่ละงานย่อยในรอบปี (ปีงบประมาณ 2555) ซึ่งผลการศึกษา พบว่า ปริมาณงานต่อปีของงาน ด้านเภสัชกรรมโรงพยาบาลของกลุ่มงานเภสัชกรรมโรงพยาบาลมัญจาคีรีเท่ากับ 30,811.95 Man - hour และสามารถวิเคราะห์ความต้องการจำนวนบุคลากร ที่ควรจะมีในการปฏิบัติงานในปริมาณงานดังกล่าว ควรจะต้องใช้บุคลากรจำนวน 18.34 คน (หรือ 19 คน) แยกตามผู้ปฏิบัติงาน คือ เภสัชกร 10.68 คน (หรือ 11 คน) เจ้าพนักงานเภสัชกรรม 7.66 คน (หรือ 8 คน) ในขณะที่มีบุคลากรปฏิบัติงาน จริง 17 คน เมื่อวิเคราะห์สถานการณ์กำลังคนในกลุ่มงานเภสัชกรรมโรงพยาบาล โดยใช้ค่าดัชนีชี้วัดความต้องการกำลังคน (WISN) เท่ากับ 0.93 แสดงให้เห็นว่า จำนวนผู้ปฏิบัติอยู่จริงในหน่วยงานมีน้อยกว่าจำนวนผู้ปฏิบัติงานที่ควรจะต้องมี Workload measurement and determination of manpower requirement in hospital pharmacy: Case study in Manchakiri Hospital, Khon Kaen Province. The objectives of this study were to measure hospital pharmacy workload and determinate manpower requirement in hospital pharmacy of Manchakiri Hospital, Khon kaen province. Hospital pharmacy activities were grouped into 8 major tasks as follows; General management and quality improvement, Drug Management, Consumer Protection, Primary Pharmaceutical Care, Clinical Pharmaceutical care, Outpatients Dispensing Services, Inpatient Dispensing Services, and Pharmaceutical Preparation. The hospital pharmacy tasks were divided to the smallest activities called elements which were performed by operators. The standard time, workload, and manpower requirement in hospital setting were measured in the year 2012. The standard time which was the time required to perform each defined element of hospital pharmacy works was determined by Expert opinion standard technique. The workload was measured by multiplying the standard time with the number of work unit of elements performed in one year period (2012). The results showed that the workload of hospital pharmacy operators were 30,811.95 man-hour. The required numbers of hospital pharmacy staffs were 18.34 persons (or 19 persons) which should be 10.68 Pharmacists (or 11 persons) and 7.66 Pharmacy technicians (or 8 persons). But there were only 17 hospital pharmacy staffs. The workload indicator of staff need was also shown under value of 1 (as 0.93) which indicated that there was the lack of the number of operators performed hospital pharmacy tasks.